Portability | portable |
---|---|
Stability | experimental |
Maintainer | libraries@haskell.org |
Lazy state monads, passing an updateable state through a computation.
Some computations may not require the full power if state transformers:
- For a read-only state, see Control.Monad.Trans.Reader.
- To accumulate a value without using it on the way, see Control.Monad.Trans.Writer.
See below for examples.
- type State s = StateT s Identity
- state :: (s -> (a, s)) -> State s a
- runState :: State s a -> s -> (a, s)
- evalState :: State s a -> s -> a
- execState :: State s a -> s -> s
- mapState :: ((a, s) -> (b, s)) -> State s a -> State s b
- withState :: (s -> s) -> State s a -> State s a
- newtype StateT s m a = StateT {
- runStateT :: s -> m (a, s)
- evalStateT :: Monad m => StateT s m a -> s -> m a
- execStateT :: Monad m => StateT s m a -> s -> m s
- mapStateT :: (m (a, s) -> n (b, s)) -> StateT s m a -> StateT s n b
- withStateT :: (s -> s) -> StateT s m a -> StateT s m a
- get :: Monad m => StateT s m s
- put :: Monad m => s -> StateT s m ()
- modify :: Monad m => (s -> s) -> StateT s m ()
- gets :: Monad m => (s -> a) -> StateT s m a
- liftCallCC :: ((((a, s) -> m (b, s)) -> m (a, s)) -> m (a, s)) -> ((a -> StateT s m b) -> StateT s m a) -> StateT s m a
- liftCallCC' :: ((((a, s) -> m (b, s)) -> m (a, s)) -> m (a, s)) -> ((a -> StateT s m b) -> StateT s m a) -> StateT s m a
- liftCatch :: (m (a, s) -> (e -> m (a, s)) -> m (a, s)) -> StateT s m a -> (e -> StateT s m a) -> StateT s m a
- liftListen :: Monad m => (m (a, s) -> m ((a, s), w)) -> StateT s m a -> StateT s m (a, w)
- liftPass :: Monad m => (m ((a, s), b) -> m (a, s)) -> StateT s m (a, b) -> StateT s m a
The State monad
type State s = StateT s IdentitySource
A parameterizable state monad where s
is the type of the state
to carry.
:: (s -> (a, s)) | pure state transformer |
-> State s a | equivalent state-passing computation |
Construct a state monad computation from a function.
(The inverse of runState
.)
:: State s a | state-passing computation to execute |
-> s | initial state |
-> (a, s) | return value and final state |
Unwrap a state monad computation as a function.
(The inverse of state
.)
:: State s a | state-passing computation to execute |
-> s | initial value |
-> a | return value of the state computation |
:: State s a | state-passing computation to execute |
-> s | initial value |
-> s | final state |
mapState :: ((a, s) -> (b, s)) -> State s a -> State s bSource
Map a stateful computation from one (return value, state) pair to another. For instance, to convert numberTree from a function that returns a tree to a function that returns the sum of the numbered tree (see the Examples section for numberTree and sumTree) you may write:
sumNumberedTree :: (Eq a) => Tree a -> State (Table a) Int sumNumberedTree = mapState (\ (t, tab) -> (sumTree t, tab)) . numberTree
withState :: (s -> s) -> State s a -> State s aSource
Apply this function to this state and return the resulting state.
The StateT monad transformer
A parameterizable state monad for encapsulating an inner monad.
The StateT Monad structure is parameterized over two things:
- s - The state.
- m - The inner monad.
Here are some examples of use:
(Parser from ParseLib with Hugs)
type Parser a = StateT String [] a ==> StateT (String -> [(a,String)])
For example, item can be written as:
item = do (x:xs) <- get put xs return x type BoringState s a = StateT s Identity a ==> StateT (s -> Identity (a,s)) type StateWithIO s a = StateT s IO a ==> StateT (s -> IO (a,s)) type StateWithErr s a = StateT s Maybe a ==> StateT (s -> Maybe (a,s))
evalStateT :: Monad m => StateT s m a -> s -> m aSource
Evaluate a state computation with the given initial state and return the final value, discarding the final state.
evalStateT
m s =liftM
fst
(runStateT
m s)
execStateT :: Monad m => StateT s m a -> s -> m sSource
Evaluate a state computation with the given initial state and return the final state, discarding the final value.
execStateT
m s =liftM
snd
(runStateT
m s)
mapStateT :: (m (a, s) -> n (b, s)) -> StateT s m a -> StateT s n bSource
Map a stateful computation from one (return value, state) pair to another. For instance, to convert numberTree from a function that returns a tree to a function that returns the sum of the numbered tree (see the Examples section for numberTree and sumTree) you may write:
sumNumberedTree :: (Eq a) => Tree a -> State (Table a) Int sumNumberedTree = mapState (\ (t, tab) -> (sumTree t, tab)) . numberTree
withStateT :: (s -> s) -> StateT s m a -> StateT s m aSource
Apply this function to this state and return the resulting state.
State operations
modify :: Monad m => (s -> s) -> StateT s m ()Source
Monadic state transformer.
Maps an old state to a new state inside a state monad. The old state is thrown away.
gets :: Monad m => (s -> a) -> StateT s m aSource
Get a specific component of the state, using a projection function supplied.
Lifting other operations
liftCallCC :: ((((a, s) -> m (b, s)) -> m (a, s)) -> m (a, s)) -> ((a -> StateT s m b) -> StateT s m a) -> StateT s m aSource
Uniform lifting of a callCC
operation to the new monad.
This version rolls back to the original state on entering the
continuation.
liftCallCC' :: ((((a, s) -> m (b, s)) -> m (a, s)) -> m (a, s)) -> ((a -> StateT s m b) -> StateT s m a) -> StateT s m aSource
In-situ lifting of a callCC
operation to the new monad.
This version uses the current state on entering the continuation.
It does not satisfy the laws of a monad transformer.
liftCatch :: (m (a, s) -> (e -> m (a, s)) -> m (a, s)) -> StateT s m a -> (e -> StateT s m a) -> StateT s m aSource
Lift a catchError
operation to the new monad.
liftListen :: Monad m => (m (a, s) -> m ((a, s), w)) -> StateT s m a -> StateT s m (a, w)Source
Lift a listen
operation to the new monad.
liftPass :: Monad m => (m ((a, s), b) -> m (a, s)) -> StateT s m (a, b) -> StateT s m aSource
Lift a pass
operation to the new monad.
Examples
A function to increment a counter. Taken from the paper Generalising Monads to Arrows, John Hughes (http://www.math.chalmers.se/~rjmh/), November 1998:
tick :: State Int Int tick = do n <- get put (n+1) return n
Add one to the given number using the state monad:
plusOne :: Int -> Int plusOne n = execState tick n
A contrived addition example. Works only with positive numbers:
plus :: Int -> Int -> Int plus n x = execState (sequence $ replicate n tick) x
An example from The Craft of Functional Programming, Simon Thompson (http://www.cs.kent.ac.uk/people/staff/sjt/), Addison-Wesley 1999: "Given an arbitrary tree, transform it to a tree of integers in which the original elements are replaced by natural numbers, starting from 0. The same element has to be replaced by the same number at every occurrence, and when we meet an as-yet-unvisited element we have to find a 'new' number to match it with:"
data Tree a = Nil | Node a (Tree a) (Tree a) deriving (Show, Eq) type Table a = [a]
numberTree :: Eq a => Tree a -> State (Table a) (Tree Int) numberTree Nil = return Nil numberTree (Node x t1 t2) = do num <- numberNode x nt1 <- numberTree t1 nt2 <- numberTree t2 return (Node num nt1 nt2) where numberNode :: Eq a => a -> State (Table a) Int numberNode x = do table <- get (newTable, newPos) <- return (nNode x table) put newTable return newPos nNode:: (Eq a) => a -> Table a -> (Table a, Int) nNode x table = case (findIndexInList (== x) table) of Nothing -> (table ++ [x], length table) Just i -> (table, i) findIndexInList :: (a -> Bool) -> [a] -> Maybe Int findIndexInList = findIndexInListHelp 0 findIndexInListHelp _ _ [] = Nothing findIndexInListHelp count f (h:t) = if (f h) then Just count else findIndexInListHelp (count+1) f t
numTree applies numberTree with an initial state:
numTree :: (Eq a) => Tree a -> Tree Int numTree t = evalState (numberTree t) []
testTree = Node "Zero" (Node "One" (Node "Two" Nil Nil) (Node "One" (Node "Zero" Nil Nil) Nil)) Nil numTree testTree => Node 0 (Node 1 (Node 2 Nil Nil) (Node 1 (Node 0 Nil Nil) Nil)) Nil
sumTree is a little helper function that does not use the State monad:
sumTree :: (Num a) => Tree a -> a sumTree Nil = 0 sumTree (Node e t1 t2) = e + (sumTree t1) + (sumTree t2)